Principal Designer's Handbook : Guide to the CDM Regulations 2015. (RIBA Publications, 2019)
The new CDM regulations came into force on 6th April 2015 changing the face of pre-construction health and safety management on construction projects, large and small. This handbook provides a comprehensive road map to undertaking the new Principal Designer role brings pre-construction health and safety risk management into the hands of architects and other designers. Offering authoritative and straightforward guidance to carrying out these tasks, it also uses case studies and checklists to demonstrate how this can be done quickly and efficiently.